Nonprofit Leadership: Translating Priorities into Mission Fulfillment - Kimberly Wiley; Dairys Montes de Oca; Colby Vasquez (EDIS, 2025)
Organizational leaders face competing priorities when making decisions that steer the focus and resources of their organization. Choosing one pathway over another requires consideration of the organization’s needs and capacities. We present four nonprofit leadership priorities central to organizational decision-making: innovativeness, staff-centered focus, strategy, and systems focus (Cameron et al., 2006). These four priorities are present in for-profit, nonprofit, and governmental organizations. Here, we apply the framework to nonprofit organizations. This publication defines the four priorities and explores their relationships. Finally, leaders will be provided tools for balancing these priorities and the associated strengths during decision-making to effectively fulfill their goals. Written by Kimberly Wiley, Dairys Montes de Oca, and Colby Vasquez, and published by the UF/IFAS Department of Family, Youth and Community Sciences, February 2025.